ANALISIS PENGARUH SEKTOR HOTEL DAN RESTORAN TERHADAP PEREKONOMIAN DI SUMATERA BARAT - Suci Nawangsari; Akhirmen Akhirmen; Joan Marta (Universitas Negeri Padang, 2015)
This study aims to: (1) analyze the role the hotel and restaurant sector to the economy in the formation of the structure of demand and the structure of supply, consumption structure, the structure of exports and imports, the structure of gross added value, (2) determine the magnitude of forward linkages and belakanh linkage to the hotel and restaurant sector, (3) determine the coefficient of deployment and dissemination sensitivity hotel and restaurant sector, (4) determine the magnitude of the multiplier effect (multiplier effect). The result shows that : (1) The contribution of hotels and restaurants output ranks last of the ten sectors, (2) Analysis of the relationship indicates that the hotel and restaurant sector have backward linkages ,(3) Analysis of the impact of the deployment where the deployment impact on the spread of and sensitivity to the coefficient of deployment, (4) The sector of hotels and restaurants have the value of the multiplier is relatively high, especially for the multiplier output and income multiplier.Keyword : hotel and restaurant, input output analysis